Seat Adjustment Design of an Intelligent Robotic Wheelchair Based on the Stewart Platform. (18th March 2013) - Hsu, Po Er; Hsu, Yeh Liang; Lu, Jun Ming; Chang, Cheng-Hao
A wheelchair user makes direct contact with the wheelchair seat, which serves as the interface between the user and the wheelchair, for much of any given day. Seat adjustment design is of crucial importance in providing proper seating posture and comfort. This paper presents a multiple-DOF (degrees of freedom) seat adjustment mechanism, which is intended to increase the independence of the wheelchair user while maintaining a concise structure, light weight, and intuitive control interface. This four-axis Stewart platform is capable of heaving, pitching, and swaying to provide seat elevation, tilt-in-space, and sideways movement functions. The geometry and types of joints of this mechanism are carefully arranged so that only one actuator needs to be controlled, enabling the wheelchair user to adjust the seat by simply pressing a button. The seat is also equipped with soft pressure-sensing pads to provide pressure management by adjusting the seat mechanism once continuous and concentrated pressure is detected. Finally, by comparing with the manual wheelchair, the proposed mechanism demonstrated the easier and more convenient operation with less effort for transfer assistance.